2022
DOI: 10.3390/ijerph191610190
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Food Literacy in the MENA Region: A Review to Inform Nutrition Research and Policy Makers

Abstract: Background: Improving food and nutrition literacy is fundamental to tackling the Middle East and North Africa (MENA) region’s enormous challenges, including malnutrition and food insecurity. To direct initiatives, it is crucial to assess the region’s food and nutrition literacy. Thus, we aimed to review studies on food/nutrition literacy status in the MENA countries and illuminate the region’s research gaps in these areas, in terms of assessment, policy, and program implementation. Methods: PubMed and Google S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 77 publications
3
21
0
Order By: Relevance
“…In Lebanon, only one preliminary study was conducted to assess the NL of adolescents and observed a lower percentage of poor NL (21.2%) than that currently reported (28). Moreover, our findings with regards to adolescents' NL is similar to that reported among Chinese (27), and Turkish adolescents (29,30). Our findings are warrantable and could be partially explained by the fact that almost all (91.0%) of the adolescents reported not receiving nutrition education in their schools' curriculum in the current study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Lebanon, only one preliminary study was conducted to assess the NL of adolescents and observed a lower percentage of poor NL (21.2%) than that currently reported (28). Moreover, our findings with regards to adolescents' NL is similar to that reported among Chinese (27), and Turkish adolescents (29,30). Our findings are warrantable and could be partially explained by the fact that almost all (91.0%) of the adolescents reported not receiving nutrition education in their schools' curriculum in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…In the MENA region, the studies addressing NL and FL status are scant so far. This is evident in a recent review (27) on the FL and NL status, which warns regional researchers to start taking incremental steps to address these concepts in the MENA region. In Lebanon, only one preliminary study was conducted to assess the NL of adolescents and observed a lower percentage of poor NL (21.2%) than that currently reported (28).…”
Section: Discussionmentioning
confidence: 99%
“…The second, third, and fifth dimensions, under the heading "The ability to operationally group foods", "the ability to calculate food serve sizes", and "the ability to prepare healthy food "refer to the understanding and use of information that, according to previous studies [1,[20][21][22] fall into the functional literacy category. The ability to operationally group foods measures a person's food literacy on the type of food groups and the principles of diversity and balance in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Nutritional Health Research Center, School of Health, Lorestan University of Medical Sciences, Khorramabad, Iran. 2 Department of Nutrition, Nutritional Health Research Center, Lorestan University of Medical Sciences, Khorramabad, Iran.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation